Renal Volumes Measured by 3‐Dimensional Sonography in Healthy Fetuses From 20 to 40 Weeks. (1st March 2013) - Yoshizaki, Carlos Tadashi; Francisco, Rossana P. V.; de Pinho, Joao Correia; Ruano, Rodrigo; Zugaib, Marcelo
Abstract : Objectives: The purpose of this study was to establish reference values for fetal kidney volumes as a function of gestational age, estimated by 3‐dimensional sonography using the Virtual Organ Computer‐Aided Analysis (VOCAL) technique (GE Healthcare, Kretztechnik, Zipf, Austria). Methods: Volumes of right and left kidneys were assessed in 213 healthy fetuses by 3‐dimensional sonography using the VOCAL technique. Inclusion criteria were healthy women with singleton pregnancies, unremarkable comprehensive fetal sonographic findings, well‐known gestational age established by first‐trimester sonography, and gestational ages between 20 and 40 weeks. Exclusion criteria were patients lost to follow‐up and birth weight abnormalities. Each patient was scanned once during pregnancy. Regression analysis was used to calculate unified formulas. Results: The mathematical models calculated in the study were as follows: expected right kidney volume = exp[–1.01 + (0.12 × gestational age)]; and expected left kidney volume = exp[–0.90 + (0.12 × gestational age)]. No significant intraobserver or inter‐observer variability was observed for the determined volumes. Conclusions: Reference values for right and left fetal kidney volumes throughout gestation using the rotational technique (VOCAL) are described. The use of this technique might aid in further definition of gestational age kidney volume standards to help in defining variations from the norm.